(Electro)chemical and antimicrobial characterization of novel Ru(II) bipyridine complexes with acetylpyridine analogs. Issue 7 (18th April 2022) - Mihajlović-Lalić, Ljiljana E.; Stanković, Dalibor; Novaković, Irena; Grgurić-Šipka, Sanja
Abstract: Three ruthenium-bipyridine complexes (1–3 ) carrying acetylpyridine ligand unit were synthesized in methanol via the reaction of [RuCl2 (bpy)2 ] with corresponding acetylpyridine (2-, 3-, and 4-acpy). Obtained complexes were characterized by ( 1 H and 13 C) NMR and IR spectroscopy, MS spectrometry, UV‒vis spectrophotometry, and cyclic voltammetry. Their structural characterization revealed bidentate coordination mode for 2-acpy while 3- and 4-acpy acted as monodentate ligands. The electrochemical profile of newly synthesized compounds was investigated by cyclic voltammetry which confirmed their electrochemical activity. Voltammetric responses within the −1.20 < Ep < 1.50 V range of potentials were summarized in two major events: Ru(II)→Ru(III) oxidation spotted at app. ΔEp = 0.65 V and successive reductions of bpy units located from ‒0.79 V to 0.47 V (vs. Ag/AgCl (3 M) electrode). The DNA-binding activity of the complexes was evaluated by both UV‒vis spectrophotometry and cyclic voltammetry indicating DNA-intercalation with a slight contribution of electrostatic interactions. Furthermore, antimicrobial activity was tested against bacterial and fungal strains, for which moderate activity was observed. Assessment of in vitro toxicity against freshly hatched nauplii of Artemia salina as well as radical scavenging capacity was evaluated. The test compounds showed neither toxicity nor antioxidant activity. Graphical Abstract: UF0001